Light Stimulation Effect on The Opening And Closing Time Of Portulaca grandiflora`s Flower ,Sesbania grandiflora`s leaves , Cassia alata`s leaves - Fauziah, Arbaul; Al Fatihah, Ainaya; Lusiana, Ika; Rohmania, Vira Azizah; AL Aziz, Zubaidah Ummah (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2021)
Light is one of external stimulations affecting the plant’s movements and causing different responses. The time of opening and closing of plant organs caused by light stimulation are different. The aim of this research was to determine the opening and closing time of Portulaca grandiflora’s flower, Sesbania grandiflora’s and Cassia alata’s leaves. The study was conducted in Madiun and Trenggalek, East Java in November 2020 using field survey and observation. The survey was carried out to obtain sample plants, while observations were to observe the opening and closing time of leaves or flower in the sample plants. The observations were carried out at 04.00 to 19.00 every 15 minutes to analyze the time range of opening and closing of flower and leaves. The opening time of Portulaca grandiflora’s flower and the Sesbania grandiflora’s leaves were almost the same, around 09.00 to 10.30. Meanwhile, the Portulaca grandiflora’s flower began to close at almost the same time as the Cassia alata’s leaves, which only 45 minutes of difference (10.45 and 10.00 respectively). The opening and closing of plant organs were influenced by light stimulation with variation time.